Surveillance, panopticism, and self-discipline in the digital age - Manokha, I (Surveillance Studies Network, 2018)
The objective of this paper is to revisit the metaphor of the Panopticon, borrowed by Michel Foucault from Jeremy Bentham to describe the development of disciplinary institutions in Western societies from the early nineteenth century, and to examine its relevance for the analysis of modern electronic means of surveillance. Widely used in the early stages of the study of new surveillance technologies, the metaphor of the Panopticon, particularly in the field of ‘surveillance studies,’ is growingly seen as inadequate to understand the impact of the latest surveillance tools and practices. This paper seeks to show that dominant interpretations of Foucault’s use of Panopticon as referring to techniques of domination or to ‘power over,’ while legitimate as regards some of his earlier writings, overlook Foucault’s later works on technologies of the self. That is, in Panoptic dispositifs in particular, as well as in settings involving power/knowledge configurations defining ‘normality’ more generally, individuals may end up exercising power over themselves without any coercion. It is argued here that the development of modern information and communication technologies may be said to produce a setting, the description of which as ‘panoptic’ is even more pertinent than was the case with respect to Western societies of the nineteenth and twentieth centuries. Building upon recent empirical works on the ‘chilling effect,’ particularly in the wake of Edward Snowden’s revelations in 2013, the article discusses modern technologies of the self—self-restraint and self-censorship—that new technologies, enabling different forms of surveillance, produce in Western societies. It also outlines the areas in which the notion of the Panopticon may be useful in terms of guiding research into self-discipline and self-restraint in the context of the proliferation of modern techniques of surveillance.